Karakteristik Penyebaran Panas Pada Sistem Transmisi Roda Gigi Dengan Termografi - Mahmudi, Ali (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2020)
Heat distribution monitoring (thermography) is one a predictive maintenance technique that can be used to determine the condition of the machine. Thermography has been widely applied, but generally for the thermal engines and heat exchangers purposes. Thermography for condition monitoring purposes of the rotating equipment including the gear transmission system are still small. Therefore further studies and research are required. The object of research is a gear transmission system that driven by an electric motor. Measurement and data collection is done by using an infrared camera to scan the heat distribution on the main components of the gear transmission system for 120 minutes operation under a load, viscosity of the lubricant and a rotation constant. Data is collected every 15 minutes after the first 30 minutes operation. The descriptive analysis and trending analysis are used in the analysis. The test results indicate that there is a significant temperature increasing on the main components of the gear transmission system. The highest temperature occurs on Â the driving motor body then followed by on the clutch, drive end motor bearings, drive end gearbox bearings, non drive endÂ gear box bearings, and on the gear box body.